The Spanish love deception - Armas, Elena ([New York] : Independently published, 2021)
"A wedding. A trip to Spain. The most infuriating man. And three days of pretending. Or in other words, a plan that will never work. Catalina Martín, (finally), not single. Her family is happy to announce that she will bring her American boyfriend to her sister's wedding. Everyone is invited to come and witness the most magical event of the year. That would certainly be tomorrow's headline in the local newspaper of the small Spanish town I came from. Or the epitaph on my tombstone, seeing the turn my life had taken in the span of a phone call. Four weeks wasn't a lot of time to find someone willing to cross the Atlantic-from NYC and all the way to Spain-for a wedding. Let alone, someone eager to play along with my charade. But that didn't mean I was desperate enough to bring the 6'4 blue eyed pain in my ass standing before me, Aaron Blackford. The man whose main occupation was making my blood boil had just offered himself to be my date. Right after inserting his nose in my business, calling me delusional, and calling himself my best option. See? Outrageous. Aggravating. Blood boiling. And much to my total despair, also right. Which left me with a surly and extra large dilemma in my hands. Was it worth the suffering to bring my colleague and bane of my existence as my fake boyfriend to my sister's wedding? Or was I better off coming clean and facing the consequences of my panic induced lie? Like my abuela would say, que dios nos pille confesados."
Keywords: Single women -- Fiction; Dating (Social customs) -- Fiction; Man-woman relationships -- Fiction; FICTION / Romance / Contemporary; Dating (Social customs); Man-woman relationships; Single women; Fiction; Romance fiction